Introducing character animation with blender - Mullen, Tony 1971- (Indianapolis, Ind. Sybex, 2011)
"Introducing Character Animation with Blender, 2nd Edition is written in a friendly but professional tone, with clear descriptions and numerous illustrative screenshots. Throughout the book, tutorials focus on how to accomplish actual animation goals, while illustrating the necessary technical methods along the way. These are reinforced by clear descriptions of how each specific aspect of Blender works and fits together with the rest of the package. By following all the tutorials, the reader will gain all the skills necessary to build and animate a well-modeled, fully-rigged character of their own. The character built over the course of the tutorials is included as a.blend file on the DVD, for the reader to experiment with and learn from. Introducing Character Animation with Blender, 2nd Edition is inspiring as well as educational. A color insert includes sample characters and frames from animations by many of the Blender community's most talented artists, which help to illustrate the impressive potential of the software"--Provided by publisher.
Keywords: Blender (Computer file).; Computer Animation; Three-dimensional display systems; Computer graphics; Computers / Image Processing